INITIAL STUDY ON THE PROSPECT OF SOLID OIL WASTE UTILIZATION FROM X FIELD AS A BASIC MATERIAL FOR ROAD ASPHALT MIXING WITH MARSHALL TEST - Erdila Indriani; Purnomosidi Purnomosidi; Rizky Martha; Bryan Ginting (Testing Center for Oil and Gas LEMIGAS, 2025)
The upstream oil and gas industry in the production sector is made up of numerous lifting activities, carried out in wells, as well as storage and sales tanks. Preliminary research has been conducted on the process of gathering systems from each point of the production facility unit to determine the pressure loss, blockage or leakage problems. The findings showed that oil spill points due to the accumulation of crude spills mixed with other sediments was approximately 2043 m3 per week. B3 waste disposal is often a burden for companies because it is expensive without revenue value, while solid waste has economic value and can be reused. Therefore, this research aimed to evaluate the use of solid waste containing 48.01% Total Petroleum Hydrocarbons (TPH), including mineral and metal sediments, namely XRD, XRF and AAS tests as basic materials for road asphalt. The result showed that the use of solid waste with a density specification of 0.92 and a Pour Point of 1700 C as the basic material for making road asphalt mixed with aggregate achieved an initial setting time of less than 5 minutes and Compressive Strength of 0.25 MPa less than the 2 MPa standard value at R20. In conclusion, the Asphalt Resin Paraffinic Sediment obtained from solid waste was less than 10% and could not be used for road asphalt hardening, hence the need to add commercial asphalt and other additives.